Assessing the relative validity of the Scottish Collaborative Group FFQ for measuring dietary intake in adults. Issue 3 (13th September 2016) - Hollis, Jenna L; Craig, Leone CA; Whybrow, Stephen; Clark, Heather; Kyle, Janet AM; McNeill, Geraldine
Abstract: Objective: To assess the relative validity of the latest version of the Scottish Collaborative Group (SCG) FFQ (version 6.6) in adults living in Scotland. Design: A cross-sectional validation study. Participants completed the self-administered, 169-item SCG FFQ followed by a 7 d, non-weighed food diary. Energy and energy-adjusted macronutrients and micronutrients were examined for relative validity through Spearman's correlation, the percentage of classification into thirds of intake, Cohen's weighted kappa ( κ w ) and Bland–Altman analysis. Setting: General population living in Scotland. Subjects: Ninety-six adults aged 18–65 years. Results: Spearman's correlation coefficients ranged from 0·21 (retinol) to 0·71 (Mg). A median of 52 % of adults were correctly classified into thirds of intake (range: 42 % (PUFA, MUFA and Fe) to 64 % (percentage energy from carbohydrates)) and 8 % were grossly misclassified into opposite thirds of intake (range: 3 % (carbohydrates, percentage energy from carbohydrates) to 19 % (thiamin)). Values of κ w ranged between 0·20 (PUFA, β-carotene) to 0·55 (percentage energy from carbohydrates). In the Bland–Altman analysis, the smallest limits of agreement, when expressed as a percentage of the mean intake from the FFQ and food diary, were seen for the main macronutrients carbohydrates, fat and protein. Conclusions: As in the previous validation study more than 10 years ago, the FFQ gave higher estimates of energy and most nutrients than the food diary, but after adjustment for energy intake the FFQ could be used in place of non-weighed food diaries for most macronutrients and many micronutrients in large-scale epidemiological studies.